NH4F-assisted one-pot solution synthesis of hexagonal ZnO microdiscs for efficient ultraviolet photodetection. Issue 9 (12th September 2018) - Li, Borui; Zhou, Kai; Chen, Zhao; Song, Zengcai; Zhang, Dong; Fang, Guojia
Abstract : One-pot solution method to grow large hexagonal ZnO microdiscs with the aid of ammonium fluoride (NH4 F) mineralizer has been realized. The size, morphology, crystallinity and optical properties of the synthesized ZnO microdiscs can be efficiently modulated by the concentration of NH4 F. X-ray diffraction and scanning electron microscopy analyses illustrate that hexagonal ZnO microdiscs achieved at 0.03 M NH4 F concentration have larger disc size and narrower full-width value at half maximum of (002) peak. It implies better crystal quality compared with those from other additive concentrations. Photoluminescence results also demonstrate the same trend. These results indicate that with proper addition of NH4 F, the crystal quality of ZnO microdiscs has been improved and defects have been suppressed. Furthermore, a UV photodetector has been fabricated by simply transferring the ZnO microdiscs grown with 0.03 M NH4 F onto a p -type silicon substrate. The device exhibits photosensitive behaviour at 365 nm UV light illuminating when −0.6 V is applied. The response time as well as recovery time is less than 0.1 s. The relatively large photoresponsivity of 1.19 A W −1 with power consumption less than 10 nW makes it possible in application field of highly efficient low power consumption UV detection.